The determinants of intention to purchase halal food products among non-Muslim consumers in Malaysia - Sharifah Husna Ayuni, Sh Hayazi (2022)
The expanding request on halal product in many countries all around the world in general enlarge the investigation about halal operation as of late as the aftereffect of quickly developing populace of Muslims around the world that amplified size of halal markets. Malaysia was one of the countries that established a halal centre in 2006 in response to the rapid growth of the global halal industry. This study examines the relationship between the product quality, product price, product availability, product ingredients, product awareness, product safety and the intention to purchase by non-Muslim consumers in Malaysia by using a sample of 135 undergraduate students in Universiti Utara Malaysia which comes from various states in Malaysia. The results of the study show evidence product quality, product availability and product safety are factors that have significant in relation toward the intention to purchase halal food products among non-Muslim consumers